Calculation and Measurement of Near-Field RCS and Received Power Using a Downscaled Model of Precision-Guided Munition - Hwang, Kyuhwan; Yoon, Daeyeong; Jo, Kyounghwan; Joo, Hyounjoon; Kim, Inbok; Kim, Honghee; Yoon, Hongsun; Kim, Jeongsub; Park, Yong Bae (Journal of Electromagnetic Engineering and Science, 2025)
This paper proposes a method for calculating received power using a downscaled model of an encounter scenario between a precisionguided munition (PGM) and a target by analyzing the near-field gain and near-field radar cross-section (RCS). Measuring the reflective properties between actual-sized targets and PGMs is a very costly and time-consuming process. Therefore, to facilitate such measurements even in a simple laboratory environment, the target encounter scenario is configured using a fixed target and a moving horn antenna in this study. The near-field gain is calculated based on the horn antenna’s physical dimensions, which varied with its distance from the target. Meanwhile, the near-field RCS is analyzed based on the magnitude of the Poynting vector, obtained through High Frequency Structure Simulator (HFSS) shooting and bouncing ray plus (SBR+) simulation. The received power is calculated by substituting the analyzed near-field gain and near-field RCS into the radar equation. In addition, the received power attained using the proposed method is compared to that obtained using far-field gain and far-field RCS, the power obtained through SBR+ simulation, and the power measured in a simple laboratory environment. An error of only 1–2 dB is observed compared to the SBR+ simulation and measured data, thereby validating the proposed downscaled model as well as the method proposed for calculating near-field gain and near-field RCS.